Prevalence and factors associated with sexual and reproductive health literacy among youth living with HIV in Uganda: a cross-sectional study - Benedicto Mugabi; Miisa Nanyingi; Richard Kabanda; Juliet Ndibazza; Peter Elyanu; John Baptist Asiimwe; Gorret Nazziwa; Gilbert Habaasa; Adeodata Kekitiinwa (BMC, 2023)
Abstract Background Adequate sexual and reproductive health literacy (SRHL) among young people has been linked to informed sexual behaviours. Studies on SRHL have largely been conducted among the general adolescent population. Little is known about youth aged 15-24 years living with human immunodeficiency virus (YLHIV). There is a possible lack of SRHL in this population, considering the high rate of teenage pregnancies and unprotected sex reported by YLHIV. This study aimed to assess the prevalence and associated personal and environmental factors for SRHL among YLHIV at a high-volume urban HIV Clinic in Uganda. Methods Through a cross-sectional survey, YLHIV receiving routine HIV care services at Baylor-Uganda HIV Clinic were interviewed using an adapted European Health Literacy Survey (HLS-EU). Using simple random sampling, eligible youth who received HIV care services between August and November 2019 were enrolled in the study. SRHL scores were computed using the HLS-EU index method; and individuals whose scores ranged from 34 to 50 were considered health literate. We used descriptive statistics to determine the prevalence. Potential associated personal and environmental factors (p<0.05) were identified by performing two-step inferential statistics, bivariate analysis and binary logistic regression. Odds ratios were calculated to estimate the likelihood of youth being health literate on sexual and reproductive health (SRH) issues in comparison with the reference categories, and 95% confidence intervals were determined to establish whether the relationships were statistically significant. Results Of the 267 YLHIV interviewed at Baylor-Uganda HIV Clinic, 167 (62.5%) were female with a mean age of 18.9 years (SD± 2.8), and the majority (242; 90.6%) were vertically infected with HIV. Only 52 (19.5%) were health literate on SRH issues. At the multivariate level, YLHIV who never had difficulty accessing SRH information were 0.391 times less likely to be health literate on SRH issues than their counterparts with challenges in accessing SRH information (Adjusted Odds Ratio [AOR] = 0.391, 95% CI =0.178 to 0.860; p= 0.019). YLHIV who did not find it easy to access SRH care service points were 2.929 times more likely to be literate in SRH than those who found it easy to access such services (Adjusted Odds Ratio [AOR] = 2.929, 95% CI =1.241 to 6.917; p=0.014). Additionally, YLHIV who did not listen to radio health talks were 2.406 times more likely to be health literate on SRH issues than those who did (AOR = 2.406, 95% CI =1.133 to 5.112; p=0.022). Conclusions SRHL is an unmet need among YLHIV; only 19.5% were health literate on SRH issues. This could complicate the achievement of the UNAIDS sustainable development goal (SDG) of an HIV/AIDS-free generation by 2030 because low health literacy (HL) skills can affect the efficacy of almost all HIV disease prevention and health promotion efforts. Inaccessible SRH care service points and not listening to radio health talks were positively associated with SRHL, while having access to SRH information was negatively associated with SRHL.